The situation of the runes in the conception of Guamán Poma de Ayala: AND THERE IS NO REMEDY! - Paucca Gonzales, Nelson (2019)
The article focuses on the explanation of the conception of Guaman Poma de Ayala, regarding the interpellation of complaints related to the disorder that the Spanish invaders had initiated in Inca society. In his writing, the author highlights three fundamental aspects: first, he describes the situation developed by the Incas before the invasion. Second, he enquires the complaints to the Spanish crown about the immoral acts that the invaders were committing against the natives, in order to summarize these facts the author coined the phrase "AND THERE IS NO REMEDY". Third, it proposes alternative solutions in order to safeguard the chaotic situation that Inca society was going through, and the author proposes to the king of Spain and Christian readers to guarantee tranquility and maintain the harmonious relationship between the Spanish crown and the runes of this society.